2021
DOI: 10.1177/00469580211064118
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Future Utilization Using Self-Reported Health and Health Conditions in a Longitudinal Cohort Study: Implications for Health Insurance Decision Support

Abstract: Decision support techniques and online algorithms aim to help individuals predict costs and facilitate their choice of health insurance coverage. Self-reported health status (SHS), whereby patients rate their own health, could improve cost-prediction estimates without requiring individuals to share personal health information or know about undiagnosed conditions. We compared the predictive accuracy of several models: (1) SHS only, (2) a “basic” model adding health-related variables, and (3) a “full” model addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It has been found that self-rated health predicts high healthcare costs in the following year better than administrative data alone, 34 and that it predicts population level risk of high expenditure. 35 This is a likely explanation for the association with the ACG variable concurrent risk. This explanation is also likely to hold for the association with unscaled total cost predicted risk, as SRH has been reported to remain fairly stable over time.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been found that self-rated health predicts high healthcare costs in the following year better than administrative data alone, 34 and that it predicts population level risk of high expenditure. 35 This is a likely explanation for the association with the ACG variable concurrent risk. This explanation is also likely to hold for the association with unscaled total cost predicted risk, as SRH has been reported to remain fairly stable over time.…”
Section: Discussionmentioning
confidence: 95%
“…Our findings showed that high scores in the ACG variables unscaled concurrent risk and unscaled total cost predicted risk and receiving a positive frailty flag were associated with reporting poor SRH. It has been found that self-rated health predicts high healthcare costs in the following year better than administrative data alone,34 and that it predicts population level risk of high expenditure 35. This is a likely explanation for the association with the ACG variable concurrent risk.…”
Section: Discussionmentioning
confidence: 99%